مدى مشروعية المظاهرة والإضراب والاعتصام فى ضوء مقاصد الشريعة - يعقوب، سركوت سروك (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
This study examines the Islamic ruling on demonstrations, strikes and sit-ins, which are means of protest, freedom of expression, and peaceful change, putting them firmly in our time, and proving their effectiveness in changing regimes in many countries. The study begins with the demonstration and clarification of the definitions, and identification of their components, and deals with disputes about the legitimacy of examining the evidence, and compares, analyzes, and weights them in light of the purposes of the law (Maqsid al Shar'iah). The study then addresses the issue of strike, its definition, and types, the different views about its legitimacy, and analyses and compares it, in light of the purposes of the law. Hunger strike is also looked at in terms of the legitimacy or the sanctity of the permissible. Then study focuses on the Shar'iah, which must be observed by all of the protesters and the authorities concerned. The results include the permissible of demonstrations, strikes and sit-ins, as an expression of opinion, enjoining what is good and forbidding what is vice, after exhausting all available ways. The protesters should adhere to a number of disciplines like the sanctity of hurting others, damage to public and private property, and other disciplines the parties concerned should comply with such as to protect the protesters, secure the roads for them, and accept their protest in the interests of the nation.